Nutrient Composition, Antioxidant and Antibacterial Activities of Ulva prolifera O. F. Müller - Arguelles, Eldrin De Los Reyes; B. Sapin, Arsenia (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan)
Seaweeds are marine organisms capable of producing diverse kinds of chemical compounds with promising pharmacological use. The study evaluated the proximate and elemental composition and the potential antioxidant (using CUPRAC, ABTS+, and DPPH assays) and antibacterial activities (using microtiter plate dilution assay) of Ulva prolifera O. F. Müller. The seaweed has a total phenolic content of 829 ± 2.00 mg GAE/g. Antioxidant efficiency of U. prolifera exerted high ability of reducing copper ions, potent ABTS+ and DPPH scavenging activities in a concentration-dependent manner with IC50 value of 24.7 mg GAE/mL, 43.52 mg GAE/mL, and 54.1 mg GAE/mL, respectively, more effective than ascorbic acid. In vitro antibacterial activity assay showed that U. prolifera exhibited inhibitory activity against bacterial pathogens such as Methicillin-resistant Staphylococcus aureus (MIC = 125 mg/mL), S. epidermidis (MIC = 125 mg/mL), and Pseudomonas fluorescens (MIC = 500 mg/mL). This investigation is the first documented report regarding antibacterial activity of U. prolifera against P. fluorescens. In addition, results showed elemental composition to be in decreasing order of Ca K Mg Na Mn Fe Zn Cu Pb Cd Cr. Proximate composition of U. prolifera showed high carbohydrate and protein content with a percentage composition of 36.20 ± 0.27% and 23.72 ± 0.31% (dry weight), respectively. This study is the first report in the Philippines that shows the potential of U. prolifera as an excellent candidate organism as source of chemical compounds with relevant application to the pharmacological industry.